The Meaning of Evaluation of Islamic Religious Education - Maspuroh; Husnul Khotimah; Irma Yuliana Nurhikmah; Salsabila Mutmainnah; Wisnu Mubarok (Penerbit Hellow Pustaka, 2024)
Evaluation in Islamic education serves several key purposes, primarily to ensure the effectiveness and quality of the educational process in institutions that focus on imparting Islamic values. The evaluation process in Islamic education is crucial for confirming that educational activities align with Islamic teachings and principles. This involves structured assessments aimed at tracking progress, identifying gaps, and fostering continuous improvement across all areas of the educational experience. The evaluation encompasses students’ cognitive, affective, and psychomotor domains. The evaluation system must be comprehensive and ongoing.